2015
DOI: 10.1159/000442425
|View full text |Cite
|
Sign up to set email alerts
|

Awake Neurophysiologically Guided versus Asleep MRI-Guided STN DBS for Parkinson Disease: A Comparison of Outcomes Using Levodopa Equivalents

Abstract: Background: Deep brain stimulation (DBS) for Parkinson's disease (PD) has traditionally been performed in awake patients. Some patients are unable to tolerate awake surgery or extensive time off their medication to allow for neurophysiological testing during traditional DBS implantation, which has previously limited surgical options for these patients. Recently, asleep image-guided lead placement using intraoperative MRI or CT for verification has been proposed as an alternative for patients unable or unwillin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 20 publications
2
35
1
Order By: Relevance
“…This is done through the fusion of the iCT scan with the preoperative MRI scan after intracranial electrode implantation . Meanwhile, other centers use an interventional MRI (iMRI) to guide placement of DBS electrodes . As an example, the DBS group at UCSF have published their experience with bilateral STN implantation in PD patients using a first‐generation MRI system (Nexframe, high‐field interventional MR‐imaging) and then the ClearPoint system (ClearPoint interventional MRI) .…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…This is done through the fusion of the iCT scan with the preoperative MRI scan after intracranial electrode implantation . Meanwhile, other centers use an interventional MRI (iMRI) to guide placement of DBS electrodes . As an example, the DBS group at UCSF have published their experience with bilateral STN implantation in PD patients using a first‐generation MRI system (Nexframe, high‐field interventional MR‐imaging) and then the ClearPoint system (ClearPoint interventional MRI) .…”
Section: Surgical Techniquementioning
confidence: 99%
“…For example, target confirmation through fusion with an iCT scan in asleep DBS surgery appears to shorten the duration of surgery . While there are few published research studies using intraoperative MRI , one reported advantage is that the intraoperative (or interventional) MRI (iMRI) approach uses near real‐time acquisition of images to prospectively guide both trajectory planning and the intended targets verification before electrode placement . Therefore, interventional MRI is most useful for DBS targets that are visible on standard clinical imaging and provides a method for objective verification of intended targets .…”
Section: Surgical Techniquementioning
confidence: 99%
“…15 Several initial series of PD patients undergoing asleep DBS have demonstrated motor and quality-of-life outcomes comparable to those in historical studies using neurophysiological testing, 9,16,22,28,29 but few reports have made direct comparisons between asleep DBS patients and control patients undergoing traditional awake surgery. 18,26 To address this gap, we report clinical outcomes for patients undergoing bilateral subthalamic nucleus (STN) or globus pallidus internus (GPi) stimulation using either awake or asleep DBS at a single institution.…”
mentioning
confidence: 99%
“…As greater comfort and experience is gained with this technique, operative times have improved. 29 In a retrospective analysis, surgical time was reduced by an average of 175 minutes if a single electrode was implanted without MER. 10 Such a reduction of the duration which a patient must remain on an operating room table has been suggested to decrease the risk of venous thrombosis and pulmonary embolism.…”
Section: Shorter Operating Timementioning
confidence: 99%
“…After 6 months of therapy, both groups showed statistically similar reductions in levodopa equivalent dosages. 29 …”
Section: Benefits Of "Asleep" Dbs Increased Patient Comfortmentioning
confidence: 99%